Assessing the spatial distribution, human perception and pro–environmental behaviour towards plastic pollution in the Nkomazi Local Municipality, Mpumalanga Province, South Africa - Matshidze, Rotondwa (Rhodes University, 2026)
Plastic pollution has been a universal issue since the industrial revolution and the problem became to be noted by scientist in the late 1960s and early 1970s within aquatic environments. Plastic waste has a significant impact on the natural environment and humans. This study aims to assess the distribution, composition, human perception, and pro–environmental behaviour towards plastic pollution in the Nkomazi Local Municipality, Mpumalanga Province, South Africa. Specifically, the study intends to assess the (i) assess the spatial distribution, abundance, and composition plastic pollutants, and (ii) assess the respondent's understanding of the effects of improper plastic disposal on the environment and assess variables that affects respondents’ choices for managing their plastic waste. The study was conducted in Nkomazi Local Municipality across three big towns (i.e., Komatipoort, Malelane, Hectorspruit), three small towns (i.e., Tonga, Kamhlushwa, Schoemansdal), and three villages (i.e., Phiva, Ntunda, Schulzendal). Firstly, a drive–by survey method was conducted to spatially locate illegal plastic dumping and enumerate the abundance and plastic composition. This was followed by 270 (30 per town/village) randomly selected household interview surveys to gather information on plastic pollution knowledge, perceptions, effects, and pro-environmental behaviours on local communities. Results show that illegal dumping of plastics was common across both urban and rural areas but was more prevalent in low–income areas in big and small towns. Most illegal plastic dumpsites were categorised as large with most of these located in big and small towns than villages. Illegal plastic dumping was common along roadsides and vacant plots, and polypropylene (PP) and polyethylene terephthalate (PET) were the most common plastic identified across most dumpsites, being more visible in rural than urban areas. Interview results show that most respondents have knowledge about plastic pollution in urban areas (both big and small towns) compared to villages. Respondents were aware of both the health and environmental effects of plastic pollution, however, knowledge of pollution effects varied across the study towns and villages. Except for the pro–environmental behaviour linked to plastic disposal procedure, most of the respondents in both urban and rural areas are unaware of the pro–environmental behaviours linked to plastic management such as recycling, separation, reuse, and participation in pro–environmental campaigns. Both sociodemographic variables (e.g., age and education level) as well as pro–environmental behaviours (e.g., reuse and sustainability) informed some of the respondents’ positive perception regarding plastic pollution. From a plastic pollution management standpoint, these results suggest (i) the need for financial investment by the municipalities towards plastic pollution reduction such as promoting reuse and recycling, (ii) measures to develop effective means of managing waste in the municipality are needed such as having waste facilities (bins) and effective waste collection time. In addition, (iii) strengthening pro–environmental attitudes and behaviour (awareness campaigns and citizen science) amongst residents of the municipality is needed to effectively manage waste pollution, and (iv) government financial and human resources investment in low–income areas because of the environmental justice mantra linked to plastic pollution. More studies are required on plastic pollution across different South African towns and cities to develop town/city specific waste management plans that are informed by human perceptions.
Keywords: Uncatalogued